THE UTILIZATION OF COOKING MAMA: LET’S COOK! APPLICATION IN WRITING PROCEDURE TEXT BY EIGHTH GRADE STUDENTS - Saut Marito Siregar (XXXXXXXX, 2022)
The objective of this study was to find out whether there was a significant effect of the utilization of Cooking Mama: Let’s Cook application in writing procedure text by eighth grade students. This research is a quantitative research with quasi-experimental design. It was carried out on eighth grade students of SMP N 3 Huta Raja Tinggi in Academic Year 2021/2022. The total number of population was 119 students and probability sampling with cluster random sampling was used to determine the sample. The total of sample was 61 students and experimental class consisted of 31 students, whereas controlled class consisted of 30 students. The writer taught both experimental and controlled classes in eight meetings. In experimental class, the writer used Cooking Mama: Let’s Cook application as a media of teaching and learning process while in controlled class the writer used conventional method. In collecting the data, a writing test of procedure text was distributed before and after the treatment. Then, the data obtained were analysed in three main steps: preliminary data (normality and homogeneity test), dependent t-test and hypothesis test. Eventually, the researcher found that tobserved was higher than ttable in the significant level of 0,05 (tobserved = 4,769 > ttable = 1,671) at the degree of freedom (df) = 59. Therefore, alternative hypothesis (Ha) was accepted and null hypothesis (H0) was rejected. It can be concluded that the utilization of Cooking Mama: Let’s Cook application gives significant effect in writing procedure text by eighth grade students. Keywords: Cooking Mama Application; Junior High School; MALL (Mobile Assisted-Language Learning); Procedure Text; Writing.